Sex tourism among Chinese men who have sex with men: a cross-sectional observational study. (October 2016) - Mao, Jessica; Tang, Weiming; Liu, Chuncheng; Wong, Ngai Sze; Tang, Songyuan; Wei, Chongyi; Tucker, Joseph
Abstract: Background: Sex tourism among men who have sex with men (MSM) provides a risk for spread of HIV and other sexually transmitted infections. Sex tourism is defined as travelling outside of one's home town and purchasing sex with gifts or money. Our objective was to characterise the frequency, sociodemographic characteristics, and sexual risk behaviours among Chinese MSM sex tourists. Methods: We undertook an online, cross-sectional survey of high-risk MSM throughout China in November, 2015. Men were invited to participate by clicking through banner adverts on social network sites. Eligible men were at least 16 years of age, had ever had anal sex with a man, and had had sex without use of a condom in the past 3 months. Questions covered sociodemographic characteristics and sexual risk behaviours. Univariate and multivariable logistic regressions were done to identify correlates of sex tourism. We also compared the mean MSM HIV prevalence in each sex tourist's origin and destination locations. Ethics approval was obtained from the ethics review boards of the Guangdong Provincial Center for Skin Diseases and STI control, the University of North Carolina at Chapel Hill, and the University of California at San Francisco. Findings: Among 1610 eligible men, 1189 (74%) completed the survey and 62 (5%) were identified as sex tourists. 20 (32%) of these men travelled primarily to purchase sex and the remainder purchased sex while travelling for another purpose. We noted little difference in sociodemographics and sexual risk behaviours between the two groups. 45 (73%) of sex tourists used a mobile app or website to find sex partners. In multivariable analyses, adjusting for age and income, sex tourism was correlated with high-risk sexual behaviours (adjusted odds ratio 1·83, 95% CI 1·06–3·17), higher income (4·44, 1·77–11·18), and living with HIV (2·79, 1·03–7·55). Sex tourism was more often from a location with a lower MSM HIV prevalence (mean prevalence 4·47, SD 2·01) to a location with a higher MSM HIV prevalence (6·86, 5·24; p<0·0001). Interpretation: MSM sex tourists were more likely to have risky sexual behaviours and travel from locations with low to high HIV prevalence rather than high to low HIV prevalence. MSM sex tourists might be part of core groups that disproportionately contribute to MSM HIV transmission. Enhanced surveillance and interventions tailored to MSM sex tourists should be considered. Funding: National Institutes of Health, Doris Duke Charitable Foundation.